2017
DOI: 10.1098/rsfs.2016.0146
|View full text |Cite
|
Sign up to set email alerts
|

Scaling properties of ageing orientation fluctuations in stripe phases

Abstract: We investigate the non-equilibrium dynamics of an ordered stripe-forming system free of topological defects. In particular, we study the ageing and the coarsening of orientation fluctuations parallel and perpendicular to the stripes via computer simulations based on a minimal phase-field model (model B with Coulomb interactions). Under the influence of noise, the stripe orientation field develops fluctuations parallel to the stripes, with the dominant modulation length λ* increasing with time as λ* ∼ and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…Our SSD measurements, which show long-range coherence extending across multiple domains to encompass the trench, only examine behavior perpendicular to the cylinder alignment. Previous studies have found that small-angle fluctuations in BCP patterns form anisotropic grains oriented orthogonally to BCP pattern. , Although inaccessible to our one-dimensional measurement technique, we expect a shorter length scale for correlations along the axis parallel to the stripes, which have predominant wavelength contributions on the order L 0 .…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Our SSD measurements, which show long-range coherence extending across multiple domains to encompass the trench, only examine behavior perpendicular to the cylinder alignment. Previous studies have found that small-angle fluctuations in BCP patterns form anisotropic grains oriented orthogonally to BCP pattern. , Although inaccessible to our one-dimensional measurement technique, we expect a shorter length scale for correlations along the axis parallel to the stripes, which have predominant wavelength contributions on the order L 0 .…”
Section: Resultsmentioning
confidence: 75%
“…Ultimately, this method provides direct experimental insight of BCP fluctuations in real time and real space, illuminating their contribution to interfacial roughness, defect healing, 39 and pattern aging. 43,44 RESULTS AND DISCUSSION SSD Imaging. To optimize our time resolution, images are acquired in the slow-scan-disabled (SSD) AFM mode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While shape and form adapt through evolution, this process is mediated by the physical forces and principles that actually shape the material. Again, this collection offers some insights, both relating to the very same forces that Thompson was considering (surface tension, [16]), as well as more complex interfacial forces [17] and interactions [18], as well as entropic principles [19] and non-equilibrium effects in pattern formation [20]. In our view, science must ultimately reconcile the geometry and forces approaches, that remain largely divorced from each other.…”
mentioning
confidence: 91%